IDENTIFIKASI DAN UJI SENSITIVITAS BAKTERI Neisseria gonorrhoeae TERHADAP ANTIBIOTIK SEFIKSIM PADA PEKERJA SEKS KOMERSIAL DI PUSKESMAS II DENPASAR SELATAN - Burhannuddin Burhannuddin (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2021)
Gonorrhea is a sexually transmitted disease caused by Neisseria gonorrhoeae. Gonorrhea infection varies greatly in the community, especially in sexually active women. Infection cases in women are often asymptomatic, that can causes complication can easily occur. The aims of this study are to identify and determine sensitivity of Neisseria gonorrhoeae bacteria against cefixime antibiotics. This study was using a descriptive method and used 30 samples. Neisseria gonorrhoeae was isolatd from the vaginal swab sample of Commercial Sex Workers at Puskesmas II Denpasar Selatan. The cultured bacteria on Thayer Martin media were then identified by gram staining, oxidase test, and catalase test. Neisseria gonorrhoeae sensitivity test against cefixime was performed by disc diffusion method. The results of identification showed that 6 (20 %) of 30 samples were Neisseria gonorrhoeae bacteria with cell characteristics in the form of diplococcus, gram-negative, oxidase and catalase positive. The results of the sensitivity test showed that all isolats of Neisseria gonorrhoeae were resistant to cefixime